Evaluation Study of Glass Fiber Reinforced Polyester and Kevlar Reinforced Polyester by Taguchi Method - Osama Sultan M. (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
In the present investigation two different types of fiber reinforced polymer composites were prepared by hand lay-up method using three different parameters (curing temperature, pressing load and fiber volume fraction). These composites were prepared from the polyester resin as the matrix material reinforced with glass fibers as first group of samples and mat Kevlar fibers as the second group, both with different volume fractions (4%, 8%, and 12%) of fibers. They were then tested by tensile strength and impact strength. The main objective in this study is to use Taguchi method for predicting the better parameters that give the better tensile and impact strength to the composites, and then preparing composites at these parameters and comparing them with the randomly used once. The experimental and analytical results showed that the Taguchi method was successful in optimizing the parameters that give the highest properties and it can find the most influential parameter regardless of the material used. Also it showed that the volume fraction was the most influential parameter on the tensile and impact strength. The difference between these composites was in the properties values and that the Kevlar composites have higher tensile and impact strength.